2018
DOI: 10.4103/0377-4929.236599
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor 2 neu expression in head and neck squamous cell cancers and its clinicopathological correlation: Results from an Indian cancer center

Abstract: In the current settings, HER2/neu is not found to be a prognostic marker in head-and-neck cancers. Standard immunohistochemistry staining protocols need to be established like in breast cancers to aid uniform reporting and further evaluate the role of this important protooncogene in head-and-neck cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…In the present study, no statistical significance was found between disease-free survival and HER2 neu expression. Studies conducted by Adnan et al [ 10 ] and Vats et al [ 19 ] showed no correlation between disease-free survival and HER2 neu expression; this correlates with the results of the present study. On the contrary, Cavalot et al [ 23 ] proved a significant association between HER2 neu expression and poor disease-free survival.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, no statistical significance was found between disease-free survival and HER2 neu expression. Studies conducted by Adnan et al [ 10 ] and Vats et al [ 19 ] showed no correlation between disease-free survival and HER2 neu expression; this correlates with the results of the present study. On the contrary, Cavalot et al [ 23 ] proved a significant association between HER2 neu expression and poor disease-free survival.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, no significant association was derived between the expression of HER2 neu and overall survival. Similar results were seen in studies conducted by Warren et al [ 25 ] and Vats et al [ 19 ]; however, Cavalot et al [ 23 ] suggested that HER2 neu expression can also be helpful in prognosis as an independent risk factor in HNSCC.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found SPINK7 up regulated in the highly invasive OSCC group, these results were similar to previous studies describing that SPINK6 was up regulated in highly metastatic tumors 43 . SPINK6 regulate the metastasis via EGFR signaling and their expression levels change during the carcinogenesis 52 .…”
Section: A-b)mentioning
confidence: 99%